Leadership Style and Organizational Justice: Does Gender Matter? (Quest Journal of Management and Social Sciences, 2023)
Purpose: This study examines the relationship between leadership style and organizational justice among bankers in commercial banks in Kathmandu Valley. It also investigates the effect of gender on the study variables.Design/Methodology/Approach: It uses a quantitative approach comprising a self-administrated questionnaire to test hypotheses from 151 bankers. Correlation and one-way analysis of variance (ANOVA) are used for data analysis.Findings: The results suggest that a positive relationship between leadership style and organizational justice exists. Moreover, it is found that there exists a significant difference between male and female bankers in transformational leadership but not in transactional leadership. Further, gender has significant differences among bankers in relation to organizational justice and its sub-dimensions.Implications: This research could help understand the importance of leadership in banks to prevail in organizational justice. It reflects the importance of creating a diverse workforce, especially the necessity of female employees to promote fairness in the organization.Keywords: Leadership style, Gender, Transactional leadership, Transformational leadership, Organizational JusticePaper Type: Research Paper